1990
DOI: 10.1203/00006450-199001000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Tidal Volume, and Mean Airway Pressure Combinations that Provide Adequate Gas Exchange and Low Alveolar Pressure during High Frequency Oscillatory Ventilation in Rabbits

Abstract: ABSTRACT. We studied healthy and saline lavaged rabbits during high frequency oscillatory ventilation to determine what combination of frequency (0, tidal volume (V,), and mean airway pressure (Fa,) produced the lowest peakto-peak alveolar pressure amplitude (Pal,) and physiologic blood gas tensions. Sinusoidal volume changes were delivered through a tracheostomy by a piston pump driven by a linear motor. Tracheal pressure amplitude (P,,) was measured through a tracheal catheter and alveolar pressure amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…Previous studies have shown that an increase in pressure amplitude increases the Vosc measured at the airway opening [6][7][8]. This study shows that this increase in Vosc can also be detected at the regional pulmonary level using EIT.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have shown that an increase in pressure amplitude increases the Vosc measured at the airway opening [6][7][8]. This study shows that this increase in Vosc can also be detected at the regional pulmonary level using EIT.…”
Section: Discussionsupporting
confidence: 52%
“…It has been suggested that ventilation and oxygenation during HFOV can be controlled independently by adjusting, respectively, the oscillation amplitude or frequency, and the continuous distending pressure (CDP) or the fraction of inspired oxygen (FI,O 2 ) [2][3][4][5][6]. An increase in oscillation amplitude at a fixed frequency will increase the oscillatory volume measured at the airway opening and improve carbon dioxide removal [7][8][9]. An increase in CDP at a fixed FI,O 2 will increase lung volume by alveolar recruitment in atelectatic lung diseases and improve oxygenation by reducing the intrapulmonary right-to-left shunt [5,10].…”
mentioning
confidence: 99%
“…There is no consensus about the ideal V T for HFOV, but studies in animals 17,18 and pre-term neonates 19 have shown that a V T of 2-3 mL/kg allows optimal gas exchange during HFOV. Although the use of these new generation neonatal ventilators is intended for the neonatal population unlike the 3100A (a ventilator that can be used with patients larger than neonates), some of them might not have sufficient power to deliver required V T for adequate gas exchange, especially when used in full-term infants at high oscillatory frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental evidence supporting the generation of small ⌬P A during HFOV was obtained in healthy adult rabbits (1) and excised adult dog lungs (2). Only one study has obtained direct measurements of ⌬P A in both a normal and abnormal lung model (3). Although the primary focus of that study was to determine whether ventilation settings could be optimized during HFOV, Kamitsuka et al (3) made an incidental observation that higher alveolar pressure amplitudes were observed during HFOV in rabbits after saline lung lavage than in the nonlavage group.…”
mentioning
confidence: 99%